2016
DOI: 10.3390/f7110263
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the Stress of Drought on Soil Respiration by Selective Thinning: Contrasting Effects of Drought on Soil Respiration of Two Oak Species in a Mediterranean Forest

Abstract: Abstract:Drought has been shown to reduce soil respiration (SR) in previous studies. Meanwhile, studies of the effect of forest management on SR yielded contrasting results. However, little is known about the combined effect of drought and forest management on SR. To investigate if the drought stress on SR can be mitigated by thinning, we implemented plots of selective thinning and 15% reduced rainfall in a mixed forest consisting of the evergreen Quercus ilex and deciduous Quercus cerrioides; we measured SR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…(1) thinning increases oak growth rates, the increase being indicative of improved light conditions and decreased competition for soil nutrient resources with spruce trees, as suggested by common oak response to thinning (Barrio Anta and varez Gonzalez 2005; Stefancik 2012); (2) the effect of thinning depends on the age, size and crown conditions of the focal trees; (3) sensitivity of oaks to summer drought increases as the thinning intensity increases (Chang et al 2016;Stojanovic et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…(1) thinning increases oak growth rates, the increase being indicative of improved light conditions and decreased competition for soil nutrient resources with spruce trees, as suggested by common oak response to thinning (Barrio Anta and varez Gonzalez 2005; Stefancik 2012); (2) the effect of thinning depends on the age, size and crown conditions of the focal trees; (3) sensitivity of oaks to summer drought increases as the thinning intensity increases (Chang et al 2016;Stojanovic et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Soil heterotrophic activity concentrates in a shallow layer, where water content quickly changes, which explains the response of heterotrophic respiration to water content. Autotrophic soil respiration depends on water root uptake from deeper layers (Chang et al 2016;Puertes et al 2019), which is why it is less sensitive to surface soil water content variations. The effect of humidity on the Rs rate may be attributed to heterotrophic microbial respiration, which is very sensitive to surface soil humidity.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors observed no effect of thinning on soil respiration (Campbell et al 2009). Chang et al (2016) indicated that Rs response to thinning was species-dependent with Rs responding less to thinning in deep-rooted species. The general review by Zhang et al (2018) reported an initial increase in Rs after light or moderate thinning intensity in broadleaved or mixed forests.…”
Section: Introductionmentioning
confidence: 90%
“…2021 ). One of the most common practices of adaptive silviculture is selective thinning, which consists of reduction of stem density ( Chang et al . 2016 ) to improve forest health and productivity by increasing the solar radiation reaching soil, soil organic matter, water and nutrient availability for the remaining trees ( Tang et al .…”
Section: Effective Forest Management Strategies For the Conservation ...mentioning
confidence: 99%